Vertebral Arteriovenous Fistula: A Rare Complication Following Transpedicular Occipitocervical Fixation in a Patient with Atlantoaxial Dislocation - Qian, Rongjun; Li, Zhixiao; Li, Ming (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2018)
Vertebral arteriovenous fistula (AVF), a complication of a vertebral artery injury (VAI), is a rare but serious complication of upper cervical spine fixation surgery. We report a case of a 59-year-old female patient who had a vertebral AVF following transpedicular occipitocervical fixation surgery. Endovascular embolization of the AVF was successfully performed using ethylene vinyl alcohol. From this case we learned that preoperative evaluation of the course of the vertebral artery is necessary, and vertebral artery embolism is an effective and safe method to treat vertebral AVF after proof of a patent second vertebral artery.
Keywords: vertebral arteriovenous fistula; vertebral artery injury; cervical spine; fixation